Creative Economy as a Catalyst for Change: A New Strategy to Alleviate Rural Poverty - Jeffriansyah Dwi Sahputra Amory (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The creative economy has been recognized as an innovative approach to addressing poverty, particularly in rural areas with limited access to conventional economic resources. This study explores the potential of the creative economy as a catalyst for change through a literature review employing a qualitative approach and descriptive analysis. Data were drawn from scholarly articles retrieved via Google Scholar from 2016 to 2024, with 22 articles selected after a rigorous screening process from an initial 43 articles. Findings reveal that the creative economy can enhance community welfare by leveraging local potentials rooted in culture, innovation, and digital technology. Case studies such as Penglipuran Tourism Village, Trusmi Village, and Kasongan Village highlight the critical roles of cross-sector collaboration, skill training, and digital infrastructure investment in supporting the success of creative economy initiatives. However, challenges such as limited technology access in rural areas and the need for sustainable policies to support creative economy growth were also identified. These findings provide significant implications for developing community empowerment strategies based on the creative economy in rural areas.